Serum inflammatory factors, vitamin D levels, and asthma severity in children with comorbid asthma and obesity/overweight: a comparative study - Jiang, Wan-yu; Jiao, Rong-hong; Ma, Su-li; Dai, Jin-sheng; Zhu, Hai-feng; Wu, Meng-ya; Che, Yan-ran; Zhang, Lei; Ding, Xiao-yuan (Frontiers in Pediatrics, 2025)
ObjectiveTo investigate serum inflammatory factors, vitamin D levels, and asthma severity in children with comorbid asthma and obesity/overweight, compared with those with asthma or obesity/overweight alone.MethodsThis retrospective comparative study included children suffering from asthma alone, asthma combined with obesity/overweight, or obesity/overweight alone at Shanghai Pudong New Area People's Hospital between January 2020 and December 2021.ResultsA total of 168 children (mean age: 4.32 ± 1.64 years; 117 males) were included. Compared with children with asthma alone (n = 56), those with comorbid asthma and obesity/overweight (n = 56) exhibited higher levels of serum levels of interleukin 6 (IL-6) (35.75 ± 24.56 vs. 15.40 ± 19.67), TNF-α (15.44 ± 7.35 vs. 12.16 ± 7.24), and leptin (3.89 ± 3.81 vs. 1.27 ± 2.31), and lower levels of 25-hydroxycholecalciferol (25-(OH) D3) (26.03 ± 10.77 vs. 37.15 ± 13.35), IL-10 (8.69 ± 2.76 vs. 15.32 ± 6.28), and IL-13 (449.40 ± 315.37 vs. 605.27 ± 351.02) (all P < 0.05). Compared with children with obese/overweight alone (n = 56), those with comorbid asthma and obesity/overweight had lower IL-10 (8.69 ± 2.76 vs. 12.29 ± 6.61) and higher IL-6 (35.75 ± 24.56 vs. 20.53 ± 17.07), IL-13 (449.40 ± 315.37 vs. 309.47 ± 257.45), and leptin (3.89 ± 3.81 vs. 2.48 ± 3.52) (all P < 0.05). Children with comorbid asthma and obesity/overweight showed higher Preschool Respiratory Assessment Measure (PRAM) scores (3.14 ± 2.40 vs. 1.93 ± 1.02, P = 0.008) and longer hospital stays (5.96 ± 1.25 vs. 5.29 ± 1.36 days, P = 0.007) compared to those with asthma alone.ConclusionsSignificant differences were observed in IL-6, IL-10, IL-13, 25-(OH) D3 levels, and leptin among children with asthma combined with obesity/overweight and those with asthma or obesity/overweight alone. Children with obesity/overweight alone displayed more severe clinical manifestations and longer hospital stays compared with those with asthma alone.